The Effects of a 10-Week Neuromuscular Training on Postural Control in Elite Youth Competitive Ballroom Dancers: A Randomized Controlled Trial - Zhang, Meiqi; Ma, Hongtao; Liu, Zhan; Smith, Daniel M.; Wang, Xiao (Frontiers in Physiology, 2021)
The purpose of this randomized controlled trial was to evaluate the efficacy of a 10-week neuromuscular training (NMT) program on the balance performance of elite youth competitive ballroom dancers. Forty-two dancers (21 couples) were randomly assigned to either the NMT group (n= 22) or the control group (CG; n = 20). Participants in NMT underwent a three-sessions-per-week NMT program for 10 weeks. Testing at baseline and after the 10 weeks intervention included the Y-balance test (YBT) and Modified-Balance Error Scoring System (MBESS). Results of YBT indicated that NMT participants demonstrated increased reach in the posterolateral and posteromedial directions for the right and left lower limb, whereas no significant change was found in the anterior direction for both limbs. Results of MBESS showed that NMT participants displayed significantly decreased errors of the double-leg floor (p = 0.026), single-leg foam (p = 0.010), double-leg foam (p = 0.003), tandem floor (p = 0.031), and tandem foam (p = 0.038), while no significant change was found in single-leg floor performance (p = 0.476). CG participants did not exhibit any significant change during the 10-week period. In summary, the study affirmed that the 10-week NMT program enhanced the balance performance of youth ballroom dancers and showed effects on ballroom dance-specific performance and lower-limb injury prevention. The results suggest that NMT may be a valuable addition to ballroom dance training regimens.